2016
DOI: 10.3847/0004-637x/819/2/153
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Spectral and Timing Properties in the Extended Burst Tails From the Magnetar 4u 0142+61

Abstract: Extended emission episodes with an intensity above the preburst level are observed following magnetar bursts from a number of soft gamma repeaters and anomalous X-ray pulsars (AXPs). Such extended tail emissions were observed following two events detected from AXP 4U 0142+61. We investigated in detail the evolution of spectral and temporal properties during these two tail segments using Rossi X-ray Timing Explorer/Proportional Counter Array observations, and report distinct variations in the spectral and tempo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The initial burst that triggered Swift/BAT on 2015 February 28, led to the detection of the decaying flux enhancement or extended tail of the source emission. Similar burst tails have been observed from other magnetars, such as; SGR 1900+14 (Lenters et al 2003), SGR 1806-20 ), SGR 1550-5418 (Şaşmaz Muş et al 2015, as well as from 4U 0142+61 in 2006 (Gavriil et al 2011, Chakraborty et al 2016). More recently, such a tail was identified following a burst from a rotation powered pulsar, PSR J1119−6127 (Göǧüş et al 2016).…”
Section: Extended Burst Tail Emissionsupporting
confidence: 79%
See 1 more Smart Citation
“…The initial burst that triggered Swift/BAT on 2015 February 28, led to the detection of the decaying flux enhancement or extended tail of the source emission. Similar burst tails have been observed from other magnetars, such as; SGR 1900+14 (Lenters et al 2003), SGR 1806-20 ), SGR 1550-5418 (Şaşmaz Muş et al 2015, as well as from 4U 0142+61 in 2006 (Gavriil et al 2011, Chakraborty et al 2016). More recently, such a tail was identified following a burst from a rotation powered pulsar, PSR J1119−6127 (Göǧüş et al 2016).…”
Section: Extended Burst Tail Emissionsupporting
confidence: 79%
“…Recently, Chakraborty et al (2016) re-analyzed the same data set and showed that these long events were bursts with extended tails, similar to those seen from SGR 1900+14 (Lenters et al 2003), SGR 1806−20 ), and SGR 1550−5418 (Muş et al 2015. Time-resolved spectral analysis of these bursts using RXTE data also revealed variable but highly prominent X-ray absorption features around 6.5 and 11 keV, and an emission line at at ∼ 13 keV only during the very early episodes of their prolonged burst tails (Chakraborty et al 2016).…”
Section: Introductionmentioning
confidence: 92%
“…Typical magnetar bursts are brief (∼0.1 s long) but very luminous, reaching peak luminosities of about 10 41 erg s −1 (Göǧüş et al 2001;Gavriil et al 2004;van der Horst et al 2012;Younes et al 2014). These constitute the bulk of burst activity, with a few intermediate bursts of about an order of magnitude more energetic, longer durations, and long-lasting tail emission, which is much weaker than the burst but significantly above the persistent emission level (Lenters et al 2003;Göǧüş et al 2011;Chakraborty et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1RXS J1708-4009 has been reported to show a phase dependent absorption line at ∼8.1 keV with σ = 0.4 keV and EW = 460 eV from the BeppoSAX observations in 1999 and 2001 (Rea et al 2003). RXTE observed 4U 0142+61 six times during outbursts from 2006 to 2007, and detected three significant emission lines at ∼4, ∼8, and ∼14 keV (Gavriil et al 2011) or three absorption lines at ∼4, ∼6.5, and ∼11 keV (Chakraborty et al 2016) from short burst spectra. However, because these features have not been reported afterwards, proton cyclotron resonance features (CRSFs) may depend on the burst activity.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…However, some observational studies suggest stronger magnetic fields on the stellar surface. Gavriil et al (2011) and Chakraborty et al (2016) reported that the surface magnetic field of 4U 0142+61 is stronger than the dipolar one. Moreover, there are reports of proton CRSFs from two low-magnetic-field sources, SGR 0418+5279 (Tiengo et al 2013) and Swift J1822.3-1606(Rodríguez Castillo et al 2016.…”
Section: Discussion and Summarymentioning
confidence: 99%